Relationship of weight change patterns from young to middle adulthood with incident rheumatoid arthritis and osteoarthritis: a retrospective cohort study - Nan, Kai; Zhang, Ming; Hu, Shouye; Shao, Xiaolong; Liu, Lin; Zhi, Yang; Xu, Peng (Frontiers in Endocrinology, 2024)
The relationship between weight change patterns and arthritis onset, specifically rheumatoid arthritis (RA) and osteoarthritis (OA), is unclear.We examined the association between weight changes from young adulthood to midlife and arthritis onset.Methods: Using data from NHANES 1999-2018, participants with self-reported arthritis were selected. Age at diagnosis determined arthritis onset. Weight change patterns were based on BMI at age 25 and 10 years before the survey. Patterns were categorized as stable non-obese, non-obese to obese, obese to non-obese, and stable obese. Cox regression models and restricted cubic spline (RCS) analysis were employed, calculating hazard ratios (HRs) and 95% confidence intervals (CIs) considering covariates.Results: Out of 20,859 participants (male 11,017, 52.82%), 4922 developed arthritis over a mean 8.66-year follow-up. Compared to stable non-obese individuals, the HRs for arthritis were 1.55 (95% CI=1.45 to 1.66, P < 0.0001) for non-obese to obese and 1.74 (95% CI=1.56 to 1.95, P < 0.0001) for stable obese. Those gaining 10-20 kg had a HR of 1.33 (95% CI=1.22 to 1.46, P < 0.0001), and gains >20 kg had a HR of 1.56 (95% CI=1.42 to 1.71, P < 0.0001), compared to stable weight (change within 2.5 kg). Identical results observed for OA and RA. RCS showed a nonlinear relationship between weight change and arthritis (all P < 0.01).Stable obesity and weight gain during adulthood increase arthritis risk. Maintaining a non-obese weight throughout adult years might reduce arthritis risk in later life.